Secondary resources recycling in building and refractory binders technology - Nagorniy, Andriy; Shabanova, Galyna; Korohodska, A.; Gaponova, Olena (Харківський національний університет будівництва та архітектури, 2016)
In connection with a lack of natural raw the expenditures for binders production are interruptedly raising. The cements obtained with secondary resources using become ones the most important hydraulically setting binders used for bonding refractory concretes. The present paper sets out the interphase interaction and hydration processes investigation results that provide the basis for industrial waste spinel cements (IWSC) technology useful to the building and refractory industries.

В умовах сьогодення у зв’язку з дефіцитом природної сировини, витрати на виробництво в’яжучих матеріалів невпинно зростають. Тому, цементи отримані з використанням вторинних ресурсів стають одними з найважливіших в’яжучих матеріалів гідравлічного тверднення для зв’язування вогнетривких бетонів. У статті представлені результати дослідження процесів міжфазної взаємодії та гідратації, які створюють основу для технології шпинельних цементів на базі промислових відходів, що використовуються у будівельної та вогнетривкої промисловості.
Keywords: spinel cement; concrete; hydration; sndustrial waste; бетон; гідратація; шпинельний цемент; промислові відходи